Exploring creativity : evaluative practices in innovation, design and the arts - Moeran, Brian, 1944-; Christensen, Bo T. (Cambridge University Press, 2013)
"Moeran and Christensen examine evaluative practices in the creative industries by exploring the processes surrounding the conception, design, manufacture, appraisal and use of creative goods. The book describes the editorial choices made by different participants in a 'creative world', as they go about conceiving, composing or designing, performing or making, selling and assessing a range of cultural products. The study draws upon ethnographically rich case studies from companies as varied as Bang and Olufsen, Hugo Boss and Lonely Planet, in order to reveal the broad range of factors guiding and inhibiting creative processes. Some of these constraints are material and technical; others social or defined by aesthetic norms. The authors explore how these various constraints affect creative work and how ultimately they contribute to the development of creativity"--